PENGARUH KUALITAS PRODUK TERHADAP VOLUME PENJUALAN PADA HOME INDUSTRI KRIPIK TEMPE “ABADI” SINGGAHAN KECAMATAN KARTOHARJO KABUPATEN MAGETAN - Izzah Yuz Rifa Widyaningrum (Universitas PGRI Madiun, 2014)
Quality is important in sales activities that need to be considered in order to meet the desires and expectations of consumers so that consumers will believe the products are made. In a study entitled